1988
DOI: 10.1159/000461822
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Procurement of Blood Coagulation Factor VIII

Abstract: Our previous studies have shown that the use of half-strength citrate anticoagulant improves plasma factor VIII stability while maintaining the viability of red cells and platelets. This study extends these observations to show that the stability of factor VIII is maintained in blood stored at room temperature or 4°C overnight and that in vitro tests indicate comparable quality of red cells and platelets prepared from half-strength citrate donations processed immediately or after overnight storage at room temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…We believe that this is due to less efficient cooling to 1-6 C in routine production, which is in agreement with the findings of Rock and Tittley [8]. Griffin et al [9] also found no statistical difference for FVIII recovery in plasma when whole blood was stored at 4 C or at room temperature, which was probably also due to the inefficient cooling at 1-6 C.…”
Section: Discussionsupporting
confidence: 91%
“…We believe that this is due to less efficient cooling to 1-6 C in routine production, which is in agreement with the findings of Rock and Tittley [8]. Griffin et al [9] also found no statistical difference for FVIII recovery in plasma when whole blood was stored at 4 C or at room temperature, which was probably also due to the inefficient cooling at 1-6 C.…”
Section: Discussionsupporting
confidence: 91%